2019
DOI: 10.1080/15622975.2019.1669822
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of pain catastrophising and specific structural and functional alterations in patients with chronic pain: Evidence in medication-overuse headache

Abstract: We examined the neuroanatomical substrate of different pain catastrophizing (PC) dimensions (i.e. rumination; magnification; helplessness) in patients with medication-overuse headache (MOH). We included 18 MOH patients who were administered the Pain Catastrophizing Scale (PCS) and scanned in a 3T-MRI. We conducted whole-brain volumetric and resting-state functional connectivity (FC) analysis to examine the association between gray matter (GM) density and FC strength and PCS dimensions controlling for depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 86 publications
(88 reference statements)
1
8
0
Order By: Relevance
“…Increasing evidence demonstrates significant relationships between pain catastrophizing and pain‐related neural activity during pain processing [for reviews, see Galambos et al (2019); Malfliet et al (2017)] in both people with chronic pain (Ellingson et al, 2018; Gracely et al, 2004; Loggia et al, 2015) and healthy individuals (Berna et al, 2010; Seminowicz & Davis, 2006), including associations with resting‐state functional connectivity (Christidi et al, 2020; Coulombe et al, 2017; Jiang et al, 2016; Kim et al, 2015; Kucyi et al, 2014; Lazaridou et al, 2017; Lee et al, 2018). However, less is known about underrepresented ethnic/race groups and to date, few brain imaging studies have investigated the relationships between psychosocial factors (e.g., pain catastrophizing) and pain‐related neural correlates (Losin et al, 2020; Terry, Tanner, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence demonstrates significant relationships between pain catastrophizing and pain‐related neural activity during pain processing [for reviews, see Galambos et al (2019); Malfliet et al (2017)] in both people with chronic pain (Ellingson et al, 2018; Gracely et al, 2004; Loggia et al, 2015) and healthy individuals (Berna et al, 2010; Seminowicz & Davis, 2006), including associations with resting‐state functional connectivity (Christidi et al, 2020; Coulombe et al, 2017; Jiang et al, 2016; Kim et al, 2015; Kucyi et al, 2014; Lazaridou et al, 2017; Lee et al, 2018). However, less is known about underrepresented ethnic/race groups and to date, few brain imaging studies have investigated the relationships between psychosocial factors (e.g., pain catastrophizing) and pain‐related neural correlates (Losin et al, 2020; Terry, Tanner, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the existence of a specific structural and functional neuroanatomical pattern in the association between rumination and MOH. 24 Some other studies examining the relationships between pain catastrophizing level, sensory processing patterns, and headache severity in adolescents with episodic migraine have indicated that elevated rumination is correlated with a higher severity of migraine pain. They also indicate a higher pain catastrophizing level in migraine patients than in healthy controls, as also seen in enhanced rumination.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the visual-FC imbalance between the DMN and CEN detected in MwoA-OA patients exhibited significant correlations with the frequency of headaches, which may indicate the deficits of inhibitory function to compensate for the effects of recurrent episodes of pain. In addition, the ITG is considered to be part of the DMN [42] and has been shown to be associated with the deterioration of pain, consistent with the PCC/PCUN [43,44]. According to the above mentioned studies, the abnormal visualrelated FC patterns may account for some clinical and psychiatric symptoms in MwoA patients, such as the frequency of headaches, cutaneous allodynia and anxiety comorbidity.…”
Section: M-oa Vs Hcsmentioning
confidence: 91%